The adverse consequences of drinking in a sample of Australian adults - Dietze, P.; Room, R.; Jolley, D.; Matthews, S.; Chikritzhs, Tanya (Informa Healthcare, 2010)
Objective: To examine the adverse consequences of drinking reported by a subsample of participants in the Australian arm of the GenACIS (Gender Alcohol and Culture: an International Study). Design and method: A random sample of adults (18+, N = 1,608) was interviewed by telephone for self-reported experience of adverse consequences of alcohol consumption. Results: Ten per cent reported experiencing either alcohol related life-area problems and/or physical/emotional/legal problems as a result of their drinking in the previous year. Around 4% reported getting into a fight after they had been drinking and 6% reported adverse effects of alcohol on their physical health. There were variations by age, and other correlates, such as drinking patterns, but not by gender. For example, while only 4% of the sample aged 35–44 reported being injured or injuring someone else, 17% of the sample aged under 25 reported being injured or injuring another. Conclusions: Young Victorians and those who reported riskier drinking were generally more likely to report experiencing adverse consequences than older Victorians and those who reported less risky drinking. This is important in the Australian context, with a focus on the harms associated with young people’s drinking the subject of much recent public debate.